Application of 30m Resolution SRTM DEM in Nepal - Jha, Raghunath (Journal of the Institute of Engineering, 2018)
Digital Terrain Model (DTM) or Digital Elevation Model (DEM) is an important data for Raster Analysis in modern GIS. Its use is extremely important for almost all fields of engineering, especially Water Resources Engineering. In Nepal, high-resolution DTM is not available, and often funds are limited to generate high-resolution DTM using modern day technology such as LiDAR or Aerial Photography. As a result most of the works are based on SRTM DEM which is available free of cost. Presently, 1arc second DTM is available in SRTM for Nepalese Territories. In this study, the applicability of 1arc second or 30m resolution SRTM is checked in comparison with the Department of Survey Digital Topographic Map. It is found that SRTM DEM performs better than DEM generated from Data available with Survey Department. Journal of the Institute of Engineering, 2018, 14(1): 235-240